The Influence of Employee Engagement and Career Development on the Organizational Commitment Of Civil Servants at the UPTD Puskesmas Sungai Ambawang - Kevin, Kevin; Arninda, Arninda (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
Organizational commitment is a crucial factor for the effectiveness and stability of public service institutions, especially in the health sector. However, disciplinary violations, fluctuations in absenteeism, and low employee engagement indicate that there needs to be more attention to the factors that influence organizational commitment. This study aims to examine the influence of employee engagement and career development on organizational commitment among civil servants at UPTD Puskesmas Sungai Ambawang. This research uses a quantitative approach with an associative design. Data were collected through distributing questionnaires to all civil servants at the Puskesmas. The analysis was conducted with validity, reliability, classical assumption test, and multiple linear regression, as well as simultaneous and partial tests. The results showed that Employee Engagement (X1) and Career Development (X2) have a positive and significant influence on Organizational Commitment (Y) both simultaneously and partially. This research contributes by examining the influence of work engagement and career development on organizational commitment in the public health sector, which is still limited in the existing literature. The findings provide a basis for policy makers in designing better human resource management strategies.